Establishment of a second monetary zone in West Africa : main report - Economic Community of West African States (Accra, Ghana : Economic Community of West African States, 2000)
The main report of a study undertaken by the ECOWAS on how the countries outside the CFA Zone could forge a cooperation arrangement to accelerate the integration of their economies within the framework of the ECOWAS Monetary Cooperation Programme.
"Economic Community of West African States"--Cover.
"Considered by the Convergence Council and adopted by the Summit of Heads of State and Government of the member states of the Fast Track Approach to Integration in ECOWAS."
oif 10/12/2014
Ref.
Keywords: Monetary unions; Money